Human Capital Formation, Income Inequality and Growth - Jean-Marie Viaene; Itzhak Zilcha (Tinbergen Institute, 2001)
The paper studies the determinants of income distribution and growth in an overlapping generations economy withheterogenous households. Our framework has the following main features:heterogeneity of consumers with respect to wealth and parental human capital;intergenerational transfers, accomplished via investment in the education of the younger generation.Heterogeneity in income results from the distribution of human capital acrossindividuals in a non-degenerate way. The human capital production is affected by 'home-education' , provided bythe parents, as well as 'public-education , which is provided equally to all young individuals of the same generation.Due to investments in human capital our economy exhibits endogenous growth. First, we explore the effects oftechnological change in human capital formation, upon the distribution of income at each date along theequilibrium path. Second, we study the impact of such technogical progress on growth and relate these results tothe income distribution inequality. Third, we provide numerical simulations to quantify the effect of changes in theparameters of the model. Simulation results include exact Gini coefficients and tax rate on labor determinedendogenously through majority voting.
Keywords: D9; E2; F2; J2; 330; Human Capital; Income Distribution; Endogenous Growth; Humankapital; Bildungsinvestition; Generationengerechtigkeit; Einkommensverteilung; Neue Wachstumstheorie; Theorie